Information, anxiety and depression in patients submitted to bone marrow transplantation (BMT) in a study of psychological intervention - Linares, Soledad De; Moratalla, Antonio; Romero, Antonio; Pablos, José María De; López, Pilar; Navarro, Pilar; Almagro, Manuel; Jurado, Manuel (Psicooncología, 2008)
At the department of Haematology on the University Hospital Virgen de las Nieves, Granada, it is applied a psychological program for patient bone marrow transplantation (BMT) candidates. With this program it is tried to favour the adjustment, to muffle the psychological impact and to determine the associated suffering. The resources are promoted to diminish the negative effects such as anxiety and depression, on the basis of the individual differences, the level of information to near the process and to it own resources of confrontation. The psychological program consists of four meetings which include: 1. Analysis and information management, 2. Confrontation skills, 3. Stress management and 4. Preparation for the isolation to family level. It is measured anxiety and depression by The Hospital Anxiety and Depression Scale (HADS), and the level information about the disease process and transplantation by a categorical scale designed for this research. The assessments are realized at following phases: the moment of diagnosis, at the revenue in chamber of isolation, at hundred days, at six months, one year and two years after BMT. Two principal groups were studied: an intervention group, which received the psychological intervention program and a control group for which did not apply the program due to the mechanics of revenue. In this work it appears as the patients who receive the psychological intervention before the transplant, they obtain minor levels in anxiety and depression; showing a level of information higher than it the patients did not receive the above mentioned intervention. These results stress the importance of psychological intervention for BMT patients.
Keywords: Psychological intervention; Anxiety; Depression; Information; Haemato¬logic patients; Bone marrow transplantation